Bee venom acupuncture for musculoskeletal pain conditions: an updated systematic review and meta-analysis - Soo-Hyun Sung; Soobin Jang; Gihyun Lee; Jang-Kyung Park; Sungjoo Lee; Byung-Cheul Shin (BMC Complementary Medicine and Therapies)
Abstract An updated systematic review of randomized controlled trials (RCTs) was conducted to evaluate the clinical evidence for the use of BVA for musculoskeletal pain. We searched 13 electronic databases up to December 2024 with no language restrictions. Since 2008, nine RCTs have been additionally identified, so a total of 20 trials were included in our updated review. In a meta-analysis of 2 RCTs, pain was significantly reduced with BVA compared to sham injection of normal saline (10-cm visual analog scale [VAS]; mean difference [MD]: -16.93; 95% confidence interval [CI] = -26.35 to -7.51, P = 0.0004, n = 85; heterogeneity: I2 = 0%). The meta-analysis of 5 RCTs comparing BVA plus acupuncture to saline injection plus acupuncture showed significant improvements in the 10-cm VAS (MD: -1.24; 95% CI = -1.63 to -0.85, P < 0.00001, n = 152; heterogeneity: I2 = 16%). No severe side effects such as anaphylaxis were observed in any of the eight trials. BVA appeared to improve musculoskeletal pain conditions compared to sham injections. However, the meta-analysis included only a limited number of RCTs with small sample sizes, and there was considerable clinical heterogeneity in terms of pain types, dosage, and concentration of BVA, which restricts the ability to draw definitive conclusions.